2010
DOI: 10.1186/1471-2121-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Low physiologic oxygen tensions reduce proliferation and differentiation of human multipotent mesenchymal stromal cells

Abstract: BackgroundHuman multipotent mesenchymal stromal cells (MSC) can be isolated from various tissues including bone marrow. Here, MSC participate as bone lining cells in the formation of the hematopoietic stem cell niche. In this compartment, the oxygen tension is low and oxygen partial pressure is estimated to range from 1% to 7%. We analyzed the effect of low oxygen tensions on human MSC cultured with platelet-lysate supplemented media and assessed proliferation, morphology, chromosomal stability, immunophenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
190
4
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(235 citation statements)
references
References 42 publications
36
190
4
5
Order By: Relevance
“…Thus, culturing MSCs under hypoxia can mimic the natural microenvironment of stem cells and allow investigations of the proliferation, differentiation, senescence, metabolic balance, and other physiological aspects of these cells, which have potentially important clinical applications (Rosová et al 2008). Previous studies mainly reported the positive effects of hypoxia on the biological characteristics of human MSCs (Saller et al 2012;Lennon et al 2001;Hung et al 2007; Grayson On the other hand, several studies showed negative or no effects of hypoxia on MSCs (Holzwarth et al 2010;Roemeling-van Rhijn et al 2013;Raheja et al 2011;Salim et al 2004;Zhu et al 2006;Malladi et al 2006). These discrepancies may be due to the variation in the oxygen tension, the duration of hypoxic culture, comparison of a limited range of biological characteristics employing a low number of MSCs, and the variation in the system that was used in each study to control the oxygen level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, culturing MSCs under hypoxia can mimic the natural microenvironment of stem cells and allow investigations of the proliferation, differentiation, senescence, metabolic balance, and other physiological aspects of these cells, which have potentially important clinical applications (Rosová et al 2008). Previous studies mainly reported the positive effects of hypoxia on the biological characteristics of human MSCs (Saller et al 2012;Lennon et al 2001;Hung et al 2007; Grayson On the other hand, several studies showed negative or no effects of hypoxia on MSCs (Holzwarth et al 2010;Roemeling-van Rhijn et al 2013;Raheja et al 2011;Salim et al 2004;Zhu et al 2006;Malladi et al 2006). These discrepancies may be due to the variation in the oxygen tension, the duration of hypoxic culture, comparison of a limited range of biological characteristics employing a low number of MSCs, and the variation in the system that was used in each study to control the oxygen level.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be due to the variation in the oxygen tension, the duration of hypoxic culture, comparison of a limited range of biological characteristics employing a low number of MSCs, and the variation in the system that was used in each study to control the oxygen level. In particular, 1 % O 2 had conflicting effects on the biological characteristics, such as proliferation, survival, and migration, of MSCs (Rosová et al 2008;Holzwarth et al 2010;Roemeling-van Rhijn et al 2013;Tsai et al 2011;Hung et al 2007;Raheja et al 2011). Therefore, to clarify the effect of hypoxia on the biological characteristics of MSCs, additional data are necessary to support these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide transcriptome and promoter methylation studies have shown that the expressed gene profile changes on culturing MSC in vitro with increased expression of, among others, cytoskeleton proteins and downregulation of cell cycle inhibitory genes [36], which is accompanied by progressive epigenetic changes [37]. There is also evidence that relatively minor changes to the culture conditions used to expand MSC, including culture at different oxygen tensions, use of fetal calf serum versus autologous serum, use of platelet lysate, or addition of growth factors (e.g., FGF2 or platelet-derived growth factor [PDGF]), affect MSC proliferation ability as well as the rate and degree of differentiation to the osteogenic, adipogenic, and chondrogenic lineages [36,[38][39][40][41]. These functional changes are associated with differences in expressed gene profile and epigenomic state of the cells [36,[38][39][40][41].…”
Section: Can In Vitro Culture Convert Germline Stem/progenitor Cellsmentioning
confidence: 99%
“…13 On the other hand, severe hypoxia can reduce these processes. 14 The influence of in vivo hypoxia, as in birth asphyxia, on the proliferation and differentiation of human UCB stem cells has not been studied. Additionally, characterization of stem cells obtained from UCB of preterm infants has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%